Leksikologiske analyser og beskrivelser ctr. leksikografiske angivelser. Bemærkninger til Undine Kramer: Lexikologisch-lexikographische Aspekte der deutschen Gegenwartssprache. Berlin 2000 - Bergenholtz, Henning (HERMES - Journal of Language and Communication in Business, 2002)
A lexicographer is not always a linguist. And a linguist is not a natural expert or semi-expert of lexicography. This is also the case for such lexicologists who see themselves as theoretical lexicographers. More important than such relationships are the negative consequences which a purely linguistic argumentation may have for lexicographical theory and practice. In many cases lexicological reviews of dictionaries and their proposals for better dictionaries are far removed from real lexicographical needs and improvements. This will be shown in a critical review of a recent publication about lexicological-lexicographical aspects.